Identification of Cuticular Pheromonal Compounds from Leaf Beetle, Alticini sp. - Sundaramahalingam, Balaji; Kannan, Amirtharaj (Asian Journal of Biological and Life Sciences, 2018)
The development of a new technique aside from insecticide spraying was necessary to control the insect pest population of agricultural crops. Insecticides are the cornerstones upon which pest management practices are based in the current civilization of farmers and are likely to remain so as long as effective and inexpensive chemicals are available. However, many insectpest management techniques using Non-lethal mechanisms for insect pest control have been successful. Therefore the study on the feasibility of disrupting communication using synthetic sex pheromone is the need of the hour. These techniques include the use of pheromones to disrupt mating. Hence the present study is focused to identify the pheromonalcuticular compounds using GC-MS, SDS-PAGE and MALDI-TOF matrix analysis. In the GC-MS analysis we found 39 compounds and the compounds such as octadecane, heptadecane, undecane, dodecane and heptacosane were reported as pheromone carrier protein in earlier studies.
Keywords: Agricultural crops; Cuticular compounds; Insecticides; Pest population; Sex pheromone